Nurses awareness and attitude towards HIV/AIDS and universal precautions: a cross-sectional study in UKMMC - A Gulifeiya,; M.A Rahmah, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Introduction : AIDS stigma and incorrect HIV/AIDS information among health care workers will influence the quality of care received by persons living with HIV/AIDS (PLHA). A cross-sectional study was conducted amongst nurses in the Hospital University Kebangsaan Malaysia (HUKM) with the objective of determining their knowledge and attitudes regarding HIV/AIDS and Universal Precautions (UP). Methods : A total of 450 female nurses were recruited in this study and data were collected via a self-administered questionnaire. Results : A total of 393 female nurses had completed the questionnaires and majority of them were Malays (95.4%) with mean age of 28.4±3.9 years old. The mean duration of work in the hospital was 6.2±3.6 years. The study results showed a satisfactory level of good knowledge among nurses (69%) and this is statistically significant (p<0.05) according to surgical or non-surgical based departments. Those working in surgical departments and those with work experience more than 6 years have higher level of knowledge compared to those from non-surgical departments. It was also found that more than half (57.3%) have positive attitude towards HIV/AIDS patients and this is significantly related (p<0.05) to their training status. Those who had been trained regarding UP have shown more positive attitudes compare to those who did not. However, this study found that knowledge level was not significantly associated with their general attitudes. Conclusion : This study showed that in general, nurses have good level of knowledge regarding HIV/AIDS and UP, and they also have positive attitude towards HIV/AIDS patients. However, being part of the health professional team, more comprehensive education programs and intervention strategies need to be implemented to improve their knowledge regarding HIV/ AIDS and UP as well as to minimize the negative attitude towards HIV/AIDS patients.